PENGARUH PERBEDAAN METODE COLD PROCESS DAN HOT PROCESS TERHADAP KARAKTERISTIK MUTU SABUN PADAT EKSTRAK BEKATUL BERAS MERAH (Oryza rufipogon Griff) - Maria Mita Susanti; Henri Dwi Septiono; Megumi Corry Susanti (Fakultas Teknik Universitas Wahid Hasyim, 2026)
Solid soap is produced through saponification, which can be done using either the cold or hot process. The key distinction lies in temperature: the cold process occurs at room temperature without heating, whereas the hot process uses heat to saponify. These differences may influence the resulting soap quality characteristics. This experimental study aimed to examine the effect of cold and hot processing methods on the quality characteristics of solid soap formulated with red rice bran extract (Oryza rufipogon Griff). The independent variable was the soap-making method, and the dependent variables were the soap's physical quality characteristics. Data were analyzed theoretically against established quality standards and statistically using an independent t-test for normally distributed data and the Mann–Whitney test for non-normal data. Both methods produced similar organoleptic properties, namely a light brown color, a chocolate-like odor, and a solid form. However, the texture differed: the cold process produced a less uniform texture, whereas the hot process produced a smoother one. Both methods yielded a pH of 8. The cold process produced 78% foam stability, 12.88% moisture content, and 0.025% free alkali, while the hot process resulted in 61% foam stability, 17.12% moisture content, and 0.022% free alkali. Statistical analysis indicated that the processing method significantly affected foam stability and moisture content (p < 0.05), but had no significant effect on pH or free alkali content (p > 0.05).